2016
DOI: 10.3136/fstr.22.307
|View full text |Cite
|
Sign up to set email alerts
|

Noodle Qualities of Fresh Pasta Supplemented with Various Amounts of Purple Sweet Potato Powder

Abstract: Sweet potato is a nutritious, cost-effective and abundantly available food crop in Asia. In an effort to utilize sweet potato for food processing, the effects of purple sweet potato powder (PSPP)-supplementation on the quality of fresh pasta was determined. Results showed that PSPP-supplementation produced fresh pasta dark purple in color, attributable to the intrinsic anthocyanin content. Moreover, PSPP provided a higher amount of gelatinized starch, resulting in softer and more elastic raw fresh pasta; and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 26 publications
0
6
0
1
Order By: Relevance
“…These results are consistent with Zhou et al, who found that sensory scores of wheat noodle, in terms of firmness, elasticity, and overall acceptability, could be improved by the use of hydrocolloids (2–4% konjac glucomannan) because of developments in textural properties such as adhesiveness as well as springiness. Santiago et al also described that higher values of cohesiveness and elasticity in noodle texture resulted in higher sensory scores in terms of taste, elasticity, and softness.…”
Section: Resultsmentioning
confidence: 97%
“…These results are consistent with Zhou et al, who found that sensory scores of wheat noodle, in terms of firmness, elasticity, and overall acceptability, could be improved by the use of hydrocolloids (2–4% konjac glucomannan) because of developments in textural properties such as adhesiveness as well as springiness. Santiago et al also described that higher values of cohesiveness and elasticity in noodle texture resulted in higher sensory scores in terms of taste, elasticity, and softness.…”
Section: Resultsmentioning
confidence: 97%
“…Wheat-flour foods have a huge amount of consumption in China and around the world. In recent years, many exogenous materials such as wheat bran, black tea, purple sweet potato powder, banana pulp and peel, seed powder, fiber, non-starch polysaccharides and soy protein, have been added into noodles, bread and steamed bread to improve their nutritional and functional properties (Du et al, 2016;Fu, Chang, & Shiau, 2015;Gökşen & Ekiz, 2016;Li, Zhu, Guo, Brijs, & Zhou, 2014;Ramli, Alkarkhi, Shin, Min-Tze, & Easa, 2009;Santiago et al, 2016;Sim, Aziah, & Cheng, 2015;Song, Zhu, Pei, Ai, & Chen, 2013;Wandee et al, 2015;Zhu, Sakulnak, & Wang, 2016). Dough modulation is the basis for preparing most wheat-flour foods.…”
Section: Introductionmentioning
confidence: 99%
“…Pengaturan ini menghasilkan mi ubi jalar dengan nilai cooking loss terendah. Semakin kecil nilai cooking loss menunjukkan semakin baik kualitas mi yang dihasilkan (Santiago et al, 2016;Mulyadi et al, 2014).…”
Section: Cooking Loss MI Ubi Jalarunclassified